Human capital and regional economic growth - Evidence from the dual approach - Enrique López-Bazo; Rosina Moreno (European Regional Science Association (ERSA), 2005)
Theoretical contributions to the literature have stressed the role of human capital in promoting economic growth. However, the empirical exercises have provided mixed evidence on the real effect of such type of capital. Most of the evidence has been obtained by estimating growth equations or production functions using samples of (heterogeneous) countries. In this paper, we report empirical evidence on the effects of human capital in the sample of Spanish regions. As they are supposed to be more homogeneous economies from an institutional, social and economic perspective, we assume that the evidence provide in this paper is a more robust measure of the real effects of human capital in stimulating the take off of lagging economies. We departure from the traditional empirical approach as our estimates come from the dual framework. This easily allows us to get not only the aggregate return to human capital, but also some other important measures such as its shadow price, that is the willingness to pay for an extra year of education of firm's employees, and the degree of complementariety/substitutability with other types of capital. Results suggest that human capital has exerted a significant effect in the Spanish regions, which is stronger in the less developed ones. It not only have a direct effect but an indirect one by compensating the mechanism of decreasing returns to physical capital. Important conclusions for the assessment and design of regional development policies can be derived from such results.
Keywords: 330